2022
DOI: 10.1021/acs.joc.2c00561
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Dearomatization Strategy to Synthesize Disubstituted 3-Isoquinolinones under Transition Metal-Free Conditions

Abstract: Herein, a one-pot protocol for constructing the disubstituted isoquinolinone derivatives via the three-component reactions of 3-haloisoquinolines, alkyl halides, and indoles under transition-metal-free conditions is described. The reaction realized the trifunctionalization of isoquinoline via a dearomatization strategy, which displayed high chemical selectivity, excellent functional group tolerance, and a wide range of substrates, and is environmentally friendly. The three-component coupling involves the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The three-component reaction of 3-haloisoquinolines 3 , alkyl halides 323 , and indoles 346 in the presence of AcONa as a base allowed the construction of disubstituted isoquinolinone derivatives 449 under metal-free conditions ( Scheme 216 ). 289 This transformation involved the trifunctionalization of the isoquinoline ring through a dearomatization strategy and it displayed high chemical selectivity and excellent functional group tolerance. Control experiments were performed in order to understand the mechanism of this transformation.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…The three-component reaction of 3-haloisoquinolines 3 , alkyl halides 323 , and indoles 346 in the presence of AcONa as a base allowed the construction of disubstituted isoquinolinone derivatives 449 under metal-free conditions ( Scheme 216 ). 289 This transformation involved the trifunctionalization of the isoquinoline ring through a dearomatization strategy and it displayed high chemical selectivity and excellent functional group tolerance. Control experiments were performed in order to understand the mechanism of this transformation.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…A series of isoquinolinone derivatives was obtained in moderate to good yields with high chemo‐selectivity and excellent functional group tolerance (Scheme 37). [45] The 3‐bromoisoquinoline 91 a reacts with benzyl bromide 92 a to give the N ‐alkylisoquinoline salt Q . This undergoes a nucleophilic attack by the hydroxide ion to genenrate the intermediate R with the release of the bromo anion.…”
Section: Brønsted Acid‐ or Base‐promoted Dearomatization Reactionsmentioning
confidence: 99%
“…In addition, Chen et al recently reported that 3-halogenated isoquinoline can be used in a one-pot approach to construct disubstituted isoquinolinone derivatives in aqueous phase. [11] Additionally, Helaja [12] prepared pyridone derivatives, utilising the directing O-benzyl groups in N-heterocycles under photogeneration conditions, while removing the protecting groups. Considering the significance of pyridones, developing novel, green synthetic strategies is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chen et al. recently reported that 3‐halogenated isoquinoline can be used in a one‐pot approach to construct disubstituted isoquinolinone derivatives in aqueous phase [11] …”
Section: Introductionmentioning
confidence: 99%